2014
DOI: 10.1111/and.12367
|View full text |Cite
|
Sign up to set email alerts
|

Joint effect of glutathione S-transferase genotypes and cigarette smoking on idiopathic male infertility

Abstract: Inconsistent results of association studies investigated the role of glutathione S-transferase genes in idiopathic male infertility may be explained by ethnical differences in gene-gene and gene-environm ent interactions. In this study, we investigated a joint contribution of GSTM1, GSTT1 and GSTP1 gene polym or phisms and cigarette smoking to the risk of idiopathic infertility in Russian men. DNA samples from 203 infertile and 227 fertile m en were genotyped by a multiplex polymerase chain reaction (GSTM1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
(57 reference statements)
2
17
0
1
Order By: Relevance
“…These findings contradict the results of the recent meta-analysis that we discussed above. [42] Indeed, among the nine case-control studies in the current meta-analysis, five studies[2627293233] showed no association between the Ile105Val polymorphism and male infertility, and three[212830] reported an increased risk, whereas only one study[31] suggested a decrease risk. The present study revealed obvious between-study heterogeneity in several genetic models.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These findings contradict the results of the recent meta-analysis that we discussed above. [42] Indeed, among the nine case-control studies in the current meta-analysis, five studies[2627293233] showed no association between the Ile105Val polymorphism and male infertility, and three[212830] reported an increased risk, whereas only one study[31] suggested a decrease risk. The present study revealed obvious between-study heterogeneity in several genetic models.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, many recent studies have been published concerning the association between the GSTP1 Ile105Val polymorphism and male infertility risk. [2126272829303233]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth to say that smoking could work on the susceptible patient having NRF2 single nucleotide polymorphism [21] . It is expected that genetic variations in major antioxidant genes will alter the susceptibility of a male to infertility and defective spermatogenesis [22] . Directly, smoking can also affect NRF2 proteins and impair antioxidant induction [23] .…”
Section: Discussionmentioning
confidence: 99%